ROMAN CATHOLIC PERSPECTIVE OF SIN AND HOMOSEXUALITY: SCRUTINIZING THE SIGNS OF THE TIMES - Nwosu, Patrick U. (UI Scholars Hub, 2020)
In a pluralistic world, in which the issues of homosexuality and gay rights have taken the centre stage of discourse in Sub-Saharan Africa, critical analysis is required to re-appraise the Roman Catholic perspective of sin and homosexuality. Again, the emergence of the study of homosexuality as a subfield within African Studies gives further vent to critical reflection to assess the merits and demerits of Church pronouncements on the issues. In the context of emerging fields of study and various sexual orientations of people of different cultures today, the issue of the Roman Catholic understanding of sin and her teaching on homosexuality has become problematic to many, especially the young ones in various higher institutions of learning. A growing number of them think that the recent comments of the Catholic Pontiff are not helping matters. The challenges seem to lie in balancing the teachings on homosexuality with the belief that God is merciful and loving. The relatively charitable disposition of the Pope calls for the re-evaluation of the Church stance on sin and homosexuality. Therefore, the paper, using historical and analytical methods, examines the basic meaning of sin and puts in context the chances of accepting homosexuals without indeed undue focus on their habits that may be in need of healing. Drawing on relevant literature and on the assertions of some students in my classes, taking RCR 332, a course in Comparative Religious Studies in the Department of Religions, University of Ilorin, Nigeria, the paper concludes that in a pluralistic society the homosexuals may make the human community richer when given the same opportunities accorded the majority orientation.